(untitled) (Research, Society and Development, 2020)
The objective of this work was to analyze the participation of the female gender in technical courses of the Federal Network in Brazil and in Amapá in 2018, by age group. The approach of this study is of a quanti-qualitative nature. The data collected came from the Plataforma Nilo Peçanha database. The results showed that both in Brazil and in the State of Amapá there was a predominance of women enrolled in educational institutes in the year 2018. At the national level, the data showed that women under the age of 20 are the majority in the Federal Institutes of Education, while in the State of Amapá the opposite was found. Nationally, in the age group of 20 to 34 the enrolled are equal. In Amapá, in the age group of 20 to 34 years, there is a slight predominance of women. The data also shows that there is a significant difference (decrease) in the percentage of women aged 50 or over in technical education. Although progress is being made, there is still much inequality between men and women and a long way to achieve gender equity.